Aluminum alloy material and preparation method thereof
By using a combination method of modified drift beads and refining agents in aluminum alloy materials, the problem of uneven distribution of reinforced phases is solved, and the high thermal conductivity and high strength of aluminum alloy materials are achieved, which improves its application range.
Patent Information
- Application Number
- CN202411649832.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-11
AI Technical Summary
There is local area accumulation or loss in the distribution of reinforced phases in the α-Al phase in existing aluminum alloy materials, which affects the uniformity of the material and cannot achieve high thermal conductivity and high strength at the same time.
By combining modified drift beads and refining agent, the primary α phase is refined by modifying drift beads, and fine crystal strengthening of the α-Al phase is combined with horizontal continuous casting and continuous extrusion molding technology. Ensure uniform distribution of the reinforced phase.
It has achieved the improvement of uniformity and comprehensive performance of aluminum alloy materials, ensured the high thermal conductivity and high strength of the material, and expanded its application range.
Smart Images

Figure BDA0005140615650000121 
Figure HDA0005140615660000011 
Figure HDA0005140615660000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy material and a preparation method thereof. Background Art
[0002] Aluminum alloy is the most widely used type of nonferrous metal structural material in industry, and has been widely used in aviation, aerospace, automobile, machinery manufacturing, shipbuilding and chemical industries. In the actual production process, according to different application fields and the required performance of aluminum alloys, metals such as magnesium, manganese, copper, zinc, and iron are added to aluminum alloys to increase the strength, rust prevention, and elongation of aluminum alloy materials. Alternatively, during the production process of aluminum alloys, a modification treatment is performed to use a refiner or increase the fine grain strengthening effect of rare earth elements on the α-Al matrix phase to increase the tensile strength, elongation, and thermal conductivity of aluminum alloys. Among them, the improvement of the crystal phase structure of aluminum alloys is the main research direction of aluminum alloy materials at present.
[0003] In the prior art, for example, in the patents such as a high-strength die-cast aluminum alloy (application number CN202010651678.1), an aluminum alloy material and its preparation method (application number CN202111381098.6), alloy modifiers (or refiners) are added in the aluminum alloy production process to greatly refine the organizational properties of the aluminum alloy, distribute it relatively evenly, avoid large internal defects, and improve the mechanical properties or thermal conductivity of the aluminum alloy. Or for example, the patent application number CN202010579815.5, named lightweight and high-strength aluminum alloy material for automobile steering knuckle, adds rare earth elements (Er) to the aluminum alloy. The Er element is added to the alloy solution to refine the α-Al phase, and the aluminum alloy product has a high yield rate, good mechanical properties, and excellent weldability.
[0004] In the above patents, the additives (rare earth elements, refiners, etc.) in the aluminum alloy production process are mainly used to achieve the refinement of the α-Al phase. However, the distribution of the strengthening phase in the aluminum alloy material in the α-Al phase still has local accumulation or missing, which affects the uniformity of the aluminum alloy material and cannot achieve good thermal conductivity and good strength at the same time, limiting the scope of use of the aluminum alloy material. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an aluminum alloy material and a preparation method thereof, which solves the problem of uneven distribution of the strengthening phase in the α-Al phase in the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solution: a method for preparing an aluminum alloy material, comprising the following steps:
[0007] (1) Weigh Si raw material, Cu raw material, Fe raw material, Mn raw material, Mg raw material, Zn raw material, and Al raw material for later use;
[0008] (2) putting the raw materials in step (1) into a melting furnace for smelting to obtain a melt;
[0009] (3) adding modified floating beads and a refiner to the melt in step (2), stirring evenly, performing horizontal continuous casting, and then performing continuous extrusion molding to obtain a molded part;
[0010] (4) The formed part in step (3) is heat treated to obtain an aluminum alloy material.
[0011] Preferably, the weight of the modified floating beads is 0.2-0.6% of the weight of the aluminum raw material; the weight of the refiner is 0.1-0.5% of the weight of the aluminum raw material.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] (1) In addition to the existing method of strengthening the α-Al phase by a refiner, the present application also adds modified floating beads, which are mainly spherical particles of SiO2 wrapped by TiO2. The spherical particles can significantly improve the fluidity of the melt, which is beneficial to the distribution of the α-Al phase and each strengthening phase (the second phase), so that the crystal phase diagram of the prepared aluminum alloy material is clear and smooth, the grain boundary is clear, there is no problem of partial phase accumulation, the network distribution is reduced, the deformation resistance of the material is ensured, the uniformity of the material is ensured, and the strength of the aluminum alloy material is improved while also ensuring that the aluminum alloy material has good thermal conductivity.
[0014] (2) At the same time, the modified floating beads can also be used as alloy modifiers, which can significantly refine the primary α phase in the aluminum alloy, serve as the core for heterogeneous nucleation, and provide more nucleation sites for the solidification of aluminum liquid. It is like building many "small strongholds" in an open space, making it easier for aluminum atoms to attach to them and start crystallization growth, thereby refining the grains and improving the strength and toughness of aluminum alloy materials.
[0015] (3) In addition, the modified floating beads themselves have a high hardness. When they are evenly dispersed in the aluminum alloy, they can play a role of dispersion strengthening. When the aluminum alloy is subjected to external force, the modified floating beads will hinder the movement of dislocations, just like setting up some "obstacles" on the road, so that the dislocations need to consume more energy to continue moving, thereby improving the strength and hardness of the aluminum alloy.
[0016] (4) Furthermore, since the modified beads have a high hardness and are distributed in the aluminum alloy matrix, when the aluminum alloy comes into friction contact with other objects, the modified beads can bear part of the friction force, reduce the wear of the aluminum alloy matrix, and improve its wear resistance.
[0017] (5) Furthermore, the refiner and modified floating beads of the present application have a synergistic effect, so that under the action of the modified floating beads, the refiner can be more evenly dispersed in the aluminum alloy. In addition to refining the α-Al phase, it can also achieve the refinement of the larger second phase, further improving the comprehensive performance of the aluminum alloy.
[0018] (6) In the present invention, Si is mainly used to improve the mechanical properties and fluidity of the alloy material, so that it is suitable for heat dissipation materials, conductive materials, etc. in the communication field. The requirements for strength are relatively low. For this reason, the content of each element in the aluminum alloy is appropriately adjusted. Among them, in order to further increase the strength of the aluminum alloy, the aluminum alloy of the present application also includes Mg, Cu, etc. for strengthening. Strengthening phases such as Mg-Si, Al-Si-Mg, Al-Cu, and Al-Mg can be formed in the aluminum alloy to improve the mechanical properties of the aluminum alloy.
[0019] Preferably, in the present invention, the modified floating beads in step (3) are prepared by a heterogeneous precipitation method using titanium sulfate as a titanium source to perform surface modification on the floating beads to obtain the modified floating beads.
[0020] Preferably, the refiner in step (3) of the present invention comprises any one of a titanium-boron refiner, an aluminum-strontium alloy refiner, an aluminum-titanium-boron alloy refiner, and a nano-TiN-Ti composite refiner.
[0021] Preferably, in step (3), the stirring speed is 300-500 r / min and the stirring time is 15-30 min.
[0022] Preferably, in the step (1), the smelting temperature is 750°C-780°C, and the smelting time is 3-6h.
[0023] Preferably, in step (4) of the present invention, the heat treatment adopts secondary aging heat treatment.
[0024] The preferred primary aging heat treatment of the present invention is: heat preservation treatment at a temperature range of 120-200°C for 2-3h, and then cooling to room temperature;
[0025] Secondary aging heat treatment: The material subjected to primary aging heat treatment is subjected to further heat preservation treatment at a temperature of 120-150°C for 5-8 hours, and then cooled to room temperature to obtain an aluminum alloy profile.
[0026] The present application also provides an aluminum alloy material, which is prepared by the above method, and includes, by weight percentage, Si: 6-8%, Cu: 0.8-1%, Fe: 0.5-1%, Mn: 0.5-0.8%, Mg: 1-1.5%, Zn: 0.4-0.6%, and the remainder is Al and unavoidable inclusions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The microstructure diagram of the aluminum alloy material of Example 1 of the present invention;
[0028] Figure 2 This is a microstructure diagram of the aluminum alloy material of Comparative Example 1 of the present invention;
[0029] Figure 3 This is a microstructure diagram of the aluminum alloy material of Comparative Example 2 in the present invention. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0031] The present application provides an aluminum alloy material, which is prepared by the above method, and in terms of weight percentage, the aluminum alloy material includes Si: 6-8%, Cu: 0.8-1%, Fe: 0.5-1%, Mn: 0.5-0.8%, Mg: 1-1.5%, Zn: 0.4-0.6%, and the balance is Al and unavoidable inclusions. Among them, the unavoidable inclusions are mainly TiO2, SiO2, Al2O3 and other components added in the subsequent production process.
[0032] The present application also provides a method for preparing an aluminum alloy material, comprising the following steps:
[0033] (1) Weigh out Si raw material, Cu raw material, Fe raw material, Mn raw material, Mg raw material, Zn raw material, and Al raw material and set aside.
[0034] In the present application, the Al raw material is an aluminum ingot with a purity of ≥99.99%, the Si raw material is a pure silicon block, the Mg raw material is a magnesium ingot, the Fe raw material is an Al-10% Fe master alloy, the Cu raw material is an Al-50% Cu master alloy, the zinc ingot with a purity of ≥99.9%, and the Mn raw material is an Al-10% Mn master alloy.
[0035] (2) Putting the raw materials in step (1) into a melting furnace for smelting to obtain a melt. When the raw materials are added to the melting furnace, the aluminum raw material is first added to the melting furnace and completely melted, and then the remaining raw materials are added in order from high to low melting points. The smelting temperature is 750°C-780°C, and the smelting time is 3-6 hours.
[0036] (3) Adding modified floating beads and a refiner to the melt in step (2), stirring evenly, performing horizontal continuous casting, and then performing continuous extrusion molding to obtain a molded part.
[0037] Among them, the modified floating beads in this application adopt a heterogeneous precipitation method, using titanium sulfate as a titanium source, to modify the surface of the floating beads to obtain modified floating beads. The specific modification process of the modified floating beads can refer to the document: Liang Yan, "Surface Modification of Floating Beads and Preparation of Composite Coatings of Floating Beads", Shenyang University, Dissertation, 2015 No. 05. The floating beads are mainly modified by the heterogeneous precipitation method to increase the density of the floating beads, so that the floating beads can be mixed with the melt under the action of stirring, ensuring that the modified floating beads can achieve the corresponding effect. The role of the refiner is basically the same as that in the prior art, and the refiner is used to refine the α-Al phase. For this purpose, the refiner can be any one of conventional titanium boron refiners, aluminum strontium alloy refiners, and aluminum titanium boron alloy refiners, or combined with the nano-TiN-Ti composite refiners recorded in the existing authorization documents. The patent document (patent application number CN202111381098.6) demonstrates through experimental comparison that nano TiN-Ti composite refiner has better enhancement effect on aluminum alloy performance than conventional titanium boron refiner. For this reason, the refiner in this application is preferably nano TiN-Ti composite refiner.
[0038] In the present application, the modified floating beads are mainly spherical particles of SiO2 wrapped by TiO2, wherein the spherical particles can significantly improve the fluidity of the melt, which is beneficial to the distribution of the α-Al phase and each reinforcing phase (the second phase), so that the crystal phase diagram of the prepared aluminum alloy material is clear and smooth, the grain boundaries are clear, there is no problem of partial phase accumulation, the network distribution is reduced, the deformation resistance of the material is ensured, and the uniformity of the material is guaranteed.
[0039] Theoretically, reducing the types of solid solution phases in aluminum alloy materials can improve the thermal conductivity of aluminum alloy materials. However, in practical applications, it is only necessary to ensure the regular arrangement of the lattice in the aluminum alloy to ensure the propagation of the lattice knitting, reduce phonon heat dissipation, and thus ensure the thermal conductivity of the aluminum alloy. At the same time, based on the presence of other strengthening phases, the aluminum alloy of the present application has better thermal conductivity and better strength, so as to expand the application of the aluminum alloy of the present application.
[0040] In order to ensure the effective mixing of the melt and the modified floating beads and the refiner, and at the same time, to ensure that the modified floating beads and the refiner can refine the initial α-Al phase, in the present application, the melt, the modified floating beads and the refiner are stirred at a speed in the range of 300-500r / min, and the stirring time is 15-30min. The temperature during the mixing process can be appropriately reduced, preferably between 700℃-720℃.
[0041] The content of modified floating beads and refiners should not be too much. If the content is too much, large blocks of primary solid solution phase will be formed, which will weaken the strengthening effect and significantly deteriorate the elongation. For this reason, in this application, the weight of modified floating beads is 0.2-0.6% of the weight of the aluminum raw material; the weight of the refiner is 0.1-0.5% of the weight of the aluminum raw material.
[0042] (4) After heat treatment of the formed part in step (3), an aluminum alloy material is obtained. The heat treatment adopts a secondary aging heat treatment. Primary aging heat treatment: after heat treatment at a temperature range of 120-200°C for 2-3 hours, water cooling or air cooling to room temperature; secondary aging heat treatment: after heat treatment at a temperature range of 120-150°C for 5-8 hours, water cooling or air cooling to room temperature, an aluminum alloy profile is obtained.
[0043] Due to the presence of soluble alloying elements in aluminum alloys, some solute atoms will be precipitated after primary aging treatment to form some small dispersed metastable phases, such as GP zone (Guinier-Preston zone) in aluminum alloys containing copper, magnesium, silicon and other elements. During secondary aging, these metastable phases will continue to transform at higher temperatures or for longer periods of time, further generating more stable precipitation phases, such as strengthening phases such as θ′ phase and S′ phase. These stable precipitation phases are of appropriate size and uniform distribution, and they will hinder the movement of dislocations. When the material is subjected to external forces, dislocations need to overcome the resistance brought by the precipitation phases in order to move, thereby increasing the strength of the aluminum alloy.
[0044] At the same time, the microstructure of aluminum alloy after primary aging still has certain instability, and some precipitated phases may continue to grow or coarsen. Secondary aging can further homogenize the structure through more reasonable temperature and time control, making the performance of each area more consistent and reducing stress concentration inside the structure. At the same time, it can promote the precipitated phase to reach a relatively stable state, avoid performance fluctuations caused by organizational changes during subsequent use, and thus improve the overall stability of aluminum alloy materials.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) In this application, the modified floating beads can also be used as alloy modifiers, which can significantly refine the primary α phase in the aluminum alloy, serve as the core of heterogeneous nucleation, and provide more nucleation sites for the solidification of aluminum liquid. It is like building many "small strongholds" in an open space, making it easier for aluminum atoms to attach to them and start crystallization growth, thereby refining the grains and improving the strength, toughness, thermal conductivity, etc. of the aluminum alloy material.
[0047] (3) In the present application, the modified floating beads themselves have a high hardness. When they are evenly dispersed in the aluminum alloy, they can play a role of dispersion strengthening. When the aluminum alloy is subjected to external force, the modified floating beads will hinder the movement of dislocations, just like setting some "obstacles" on the road, so that the dislocations need to consume more energy to continue moving, thereby improving the strength and hardness of the aluminum alloy.
[0048] (4) In the present application, since the modified beads have a high hardness and are distributed in the aluminum alloy matrix, when the aluminum alloy comes into frictional contact with other objects, the modified beads can bear part of the friction force, reduce the wear of the aluminum alloy matrix, and improve its wear resistance.
[0049] (5) In the present application, the refiner and the modified floating beads of the present application also have a synergistic effect, so that under the action of the modified floating beads, the refiner can be more evenly dispersed in the aluminum alloy. In addition to refining the α-Al phase, it can also achieve the refinement of the larger second phase, further improving the comprehensive performance of the aluminum alloy.
[0050] (6) In the present invention, Si is mainly used to improve the mechanical properties and fluidity of the alloy material, so that it is suitable for heat dissipation materials, conductive materials, etc. in the communication field. The requirements for strength are relatively low. For this reason, the content of each element in the aluminum alloy is appropriately adjusted. Among them, in order to further increase the strength of the aluminum alloy, the aluminum alloy of the present application also includes Mg, Cu, etc. for strengthening. Strengthening phases such as Mg-Si, Al-Si-Mg, Al-Cu, and Al-Mg can be formed in the aluminum alloy to improve the mechanical properties of the aluminum alloy.
[0051] Example 1
[0052] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 6%, Cu: 1%, Fe: 1%, Mn: 0.8%, Mg: 1.5%, Zn: 0.6%, and the remainder is Al and unavoidable inclusions.
[0053] The preparation method of the aluminum alloy material comprises the following steps:
[0054] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 750°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt. When the melt is cooled to 700°C, the melt is mixed with 0.2% of the modified floating beads by weight of the aluminum raw material and 0.5% of the nano-TiN / Ti composite refiner by weight of the aluminum raw material, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 120°C for 2 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 150°C for 5 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0055] Example 2
[0056] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 7%, Cu: 0.8%, Fe: 0.5%, Mn: 0.6%, Mg: 1.2%, Zn: 0.4%, and the remainder is Al and unavoidable inclusions.
[0057] The preparation method of the aluminum alloy material comprises the following steps:
[0058] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are ready for use. At 780°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 4 hours to obtain a melt. When the melt is cooled to 720°C, the melt is mixed with 0.6% of the modified floating beads by weight of the aluminum raw material and 0.1% of the titanium boron refiner by weight of the aluminum raw material, and stirred for 20 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 160°C for 2.5 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 120°C for 6 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0059] Example 3
[0060] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 8%, Cu: 0.9%, Fe: 0.8%, Mn: 0.5%, Mg: 1%, Zn: 0.5%, and the remainder is Al and unavoidable inclusions.
[0061] The preparation method of the aluminum alloy material comprises the following steps:
[0062] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 760°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt. When the melt is cooled to 710°C, the melt is mixed with 0.4% of the modified floating beads by weight of the aluminum raw material and 0.3% of the aluminum strontium alloy refiner by weight of the aluminum raw material, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 120°C for 2 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 150°C for 5 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0063] Example 4
[0064] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 6%, Cu: 1%, Fe: 1%, Mn: 0.8%, Mg: 1.5%, Zn: 0.6%, and the remainder is Al and unavoidable inclusions.
[0065] The preparation method of the aluminum alloy material comprises the following steps:
[0066] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 750°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt. When the melt is cooled to 720°C, the melt is mixed with 0.2% of the modified floating beads by weight of the aluminum raw material and 0.5% of the aluminum titanium boron alloy refiner by weight of the aluminum raw material, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 120°C for 2 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 150°C for 5 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0067] Comparative Example 1
[0068] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 6%, Cu: 1%, Fe: 1%, Mn: 0.8%, Mg: 1.5%, Zn: 0.6%, and the remainder is Al and unavoidable inclusions.
[0069] The preparation method of the aluminum alloy material comprises the following steps:
[0070] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 750°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt; when the melt is cooled to 700°C, the melt and 0.5% of the mass of the aluminum raw material nano-TiN / Ti composite refiner are mixed, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The molded part is subjected to secondary aging heat treatment. The primary aging heat treatment: after heat preservation treatment at a temperature range of 120°C for 2 hours, water cooling or air cooling is used to cool to room temperature; the secondary aging heat treatment: the material subjected to the primary aging heat treatment is further heat preserved at a temperature range of 150°C for 5 hours, and then water cooling or air cooling is used to cool to room temperature to obtain an aluminum alloy profile.
[0071] Comparative Example 2
[0072] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 6%, Cu: 1%, Fe: 1%, Mn: 0.8%, Mg: 1.5%, Zn: 0.6%, and the remainder is Al and unavoidable inclusions.
[0073] The preparation method of the aluminum alloy material comprises the following steps:
[0074] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are ready for use. At 750°C, the aluminum ingots are first added to the smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt; when the melt is cooled to 720°C, the melt is stirred at a stirring speed of 300-500r / min for 15 minutes. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The molded part is subjected to secondary aging heat treatment. The primary aging heat treatment: after heat preservation treatment at a temperature range of 120°C for 2 hours, water cooling or air cooling is used to cool to room temperature; the secondary aging heat treatment: the material subjected to the primary aging heat treatment is heat preserved at a temperature range of 150°C for 5 hours, and then water cooling or air cooling is used to cool to room temperature to obtain an aluminum alloy profile.
[0075] Comparative Example 3
[0076] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 6%, Cu: 1%, Fe: 1%, Mn: 0.8%, Mg: 1.5%, Zn: 0.6%, and the remainder is Al and unavoidable inclusions.
[0077] The preparation method of the aluminum alloy material comprises the following steps:
[0078] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 750°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt. When the melt is cooled to 700°C, the melt is mixed with 1% of the modified floating beads by mass of the aluminum raw material and 0.5% of the nano-TiN / Ti composite refiner by mass of the aluminum raw material, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 120°C for 2 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 150°C for 5 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0079] Comparative Example 4
[0080] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 6%, Cu: 1%, Fe: 1%, Mn: 0.8%, Mg: 1.5%, Zn: 0.6%, and the remainder is Al and unavoidable inclusions.
[0081] The preparation method of the aluminum alloy material comprises the following steps:
[0082] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 750°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt. When the melt is cooled to 700°C, the melt is mixed with 0.2% of the modified floating beads by weight of the aluminum raw material and 1% of the nano-TiN / Ti composite refiner by weight of the aluminum raw material, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 120°C for 2 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 150°C for 5 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0083] Comparative Example 5
[0084] Calculated by weight percentage, the chemical composition of the aluminum alloy material in this embodiment is: Si: 9%, Cu: 0.3%, Fe: 0.4%, Mn: 0.2%, Mg: 0.5%, Zn: 0.2%, and the remainder is Al and unavoidable inclusions.
[0085] The preparation method of the aluminum alloy material comprises the following steps:
[0086] Aluminum ingots, pure silicon blocks, magnesium ingots, Al-10% Fe master alloys, Al-50% Cu master alloys, Al-10% Mn master alloys and zinc ingots are prepared. At 750°C, the aluminum ingots are first added to a smelting furnace for complete melting, and then the remaining raw materials are added in order of melting point from high to low, and smelted for 3 hours to obtain a melt. When the melt is cooled to 720°C, the melt is mixed with 0.2% of the modified floating beads by weight of the aluminum raw material and 0.5% of the nano-TiN / Ti composite refiner by weight of the aluminum raw material, and stirred for 15 minutes at a stirring speed of 300-500r / min. Then, horizontal continuous casting is performed, and then continuous extrusion molding is performed to obtain a molded part. The formed parts are subjected to secondary aging heat treatment. The primary aging heat treatment is as follows: after the material is kept at a temperature of 120°C for 2 hours, it is cooled to room temperature by water or air; the secondary aging heat treatment is as follows: after the material subjected to the primary aging heat treatment is kept at a temperature of 150°C for 5 hours, it is cooled to room temperature by water or air to obtain an aluminum alloy profile.
[0087] Performance Test:
[0088] 1. The ultimate tensile strength and elongation at room temperature refer to GB / T228.1-2010 "Tensile Test Methods for Metallic Materials" and are tested using a universal testing machine.
[0089] 2. The conductivity is tested using the four-electrode method. The conductivity of standard annealed pure copper is generally defined as 100% IACS.
[0090] 3. The measurement method of thermal conductivity is the national standard: GB / T3651-2008.
[0091] 4. Brinell hardness: The method for measuring hardness is the national standard: GB / T231. Use HB-3000C Brinell hardness tester to measure hardness. The pressure load is 250kg, the pressure head diameter is 5mm, and the holding time is 15s. Each hardness value is the average of 4 measurements.
[0092] 5. Use MFT4000 multifunctional material surface performance tester with a load of 5N, a friction speed of 100mm / min, a friction length of 5mm, a time of 20min, a test sample size of φ10×15mm, and use an electronic analytical scale to weigh the mass before and after the friction and wear test and calculate the wear loss weight.
[0093] The above test results are shown in Table 1.
[0094] Table 1 Performance test results of products prepared in Examples and Comparative Examples
[0095]
[0096] According to the data in Table 1, we can see that:
[0097] (1) According to the data of Example 1 and Comparative Example 5, it can be seen that there is basically no difference in the thermal conductivity values of the two, and the difference between Comparative Example 1 and Example 1 is only that the composition of the aluminum alloy is different. Comparative Example 1 adopts the combination method in the prior art, mainly with Si as the main added element, to minimize the influence of the addition of intermediate alloy elements on the thermal conductivity of the aluminum alloy, and obtain an aluminum alloy material with high thermal conductivity. However, in the present application, even if multiple components are used in Example 1, under the action of modified floating beads, the regular arrangement of the lattice in the aluminum alloy can ensure the propagation of the lattice knitting, reduce phonon heat dissipation, and thus ensure the thermal conductivity of the aluminum alloy. At the same time, combined with the strength performance of the two, it can be seen that the data of Example 1 is better than the data of Comparative Example 1. For this reason, it can be demonstrated that by adding modified floating beads in the present application, the uniformity of the aluminum alloy material can be improved and the comprehensive performance of the aluminum alloy can be improved.
[0098] (2) According to the data of Example 1, Example 4 and Comparative Example 1, Comparative Example 2, it can be seen that the type of refiner has some influence on the comprehensive performance of the aluminum alloy. However, under the action of the modified floating beads, the influence of the refiner can be reduced as much as possible and the comprehensive performance of the product can be improved.
[0099] (3) According to the data of Example 1 and Comparative Examples 3 and 4, it can be seen that the content of modified floating beads and refiners should not be too much. If the content is too much, large blocks of primary solid solution phase will be formed, which will weaken the strengthening effect and significantly deteriorate the elongation.
[0100] (4) The aluminum alloy material of the present application adopts a secondary aging heat treatment, which improves the mechanical properties of the aluminum alloy profile and makes the aluminum alloy material have high strength and good wear resistance, which is conducive to expanding the application scope of the aluminum alloy material.
[0101] 6. The aluminum alloy materials of Example 1 and Comparative Examples 1-2 were subjected to microstructural tests. The test results are as follows: Figure 1-3 shown.
[0102] Depend on Figure 1 It can be seen that in the aluminum alloy material of Example 1, the α-Al dendrites are equiaxed, the growth of grains in all directions is relatively balanced, and the strength, hardness and toughness of the aluminum alloy are slightly different in different directions, thereby ensuring the stability of the aluminum alloy material; at the same time, the formed reinforcement phase is uniformly dispersed in the matrix to achieve the purpose of dispersion strengthening, and the reinforcement phase particles can hinder dislocation movement, produce a dispersion strengthening effect, and improve the strength of the aluminum alloy; and, the uniformly distributed reinforcement phase can improve the stability of the aluminum alloy in special environments such as high temperature, prevent grain growth or organizational transformation, thereby maintaining better performance.
[0103] Depend on Figure 2It can be seen that the α-Al dendrites in the aluminum alloy material in Comparative Example 1 are partially equiaxed and partially dendritic, and there is also a large second phase, indicating that the uniformity of the alloy material in Comparative Example 1 is not good, resulting in the mechanical properties of the material being lower than those of the alloy material in Example 1, indicating that the modified floating beads can improve the uniformity of the aluminum alloy material and provide comprehensive performance of the material.
[0104] Figure 3 The α-Al phase grain effect diagram is equivalent to the conventional conditions. It can be seen that without adding refiners and modified floating beads, the metallographic diagram presents a complex polycrystalline structure. The image contains a large number of irregularly shaped grains, which are of different sizes and unevenly distributed, resulting in poor bonding of the strengthening phases. Combined with the data in Table 1, it can be seen that conventional molten alloys do not have a significant effect on improving the performance of aluminum alloys.
[0105] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing an aluminum alloy material, characterized in that: The steps include: (1) Weigh Si raw material, Cu raw material, Fe raw material, Mn raw material, Mg raw material, Zn raw material, and Al raw material for later use; (2) putting the raw materials in step (1) into a melting furnace for smelting to obtain a melt; (3) adding modified floating beads and a refiner to the melt in step (2), stirring evenly, performing horizontal continuous casting, and then performing continuous extrusion molding to obtain a molded part; (4) The formed part in step (3) is heat treated to obtain an aluminum alloy material.
2. The preparation method according to claim 1, characterized in that: The weight of the modified floating beads is 0.2-0.6% of the weight of the aluminum raw material; the weight of the refiner is 0.1-0.5% of the weight of the aluminum raw material.
3. The method for preparing the aluminum alloy material according to claim 1 or 2, characterized in that: The modified floating beads in step (3) are prepared by a heterogeneous precipitation method using titanium sulfate as a titanium source to perform surface modification on the floating beads to obtain modified floating beads.
4. The preparation method according to claim 1, characterized in that: The refiner in step (3) includes any one of a titanium-boron refiner, an aluminum-strontium alloy refiner, an aluminum-titanium-boron alloy refiner, and a nano-TiN-Ti composite refiner.
5. The preparation method according to claim 3, characterized in that: The refiner in step (3) includes any one of a titanium-boron refiner, an aluminum-strontium alloy refiner, an aluminum-titanium-boron alloy refiner, and a nano-TiN-Ti composite refiner.
6. The preparation method according to claim 1, characterized in that: In step (3), the stirring speed is 300-500 r / min and the stirring time is 15-30 min.
7. The preparation method according to claim 1, characterized in that: The smelting temperature in step (1) is 750°C-780°C, and the smelting time is 3-6h.
8. The preparation method according to claim 1, characterized in that: In step (4), the heat treatment adopts secondary aging heat treatment.
9. The preparation method according to claim 8, characterized in that: Primary aging heat treatment: After heat treatment at a temperature range of 120-200℃ for 2-3h, cool to room temperature; Secondary aging heat treatment: The material subjected to primary aging heat treatment is subjected to heat preservation treatment at a temperature range of 120-150°C for 5-8 hours, and then cooled to room temperature to obtain an aluminum alloy profile.
10. An aluminum alloy material, characterized in that: Prepared according to any of the preparation methods described in claims 1-9, and Calculated in weight percentage, the aluminum alloy material includes Si: 6-8%, Cu: 0.8-1%, Fe: 0.5-1%, Mn: 0.5-0.8%, Mg: 1-1.5%, Zn: 0.4-0.6%, and the balance is Al and unavoidable inclusions.
Citation Information
Patent Citations
High-strength die-casting aluminum alloy
CN111733352A
Aluminum alloy material for light-weight and high-strength automobile steering knuckle
CN111850364A
Aluminum alloy material and preparation method thereof
CN114058914A
Cited By
High-strength aluminum alloy for solar photovoltaic frame and preparation method thereof
CN120330549A